ANALISIS POTENSI PENGEMBANGAN BUDIDAYA IKAN KERAMBA ADAPTIF DI WILAYAH PESISIR - Heri - Ariadi; Hayati Soeprapto; Juita Lusiana Sihombing; Wafiq Khairina (JURNAL PERIKANAN TROPIS, 2022)
Fish farming with adaptive cages is an alternative for developing fishery business activities in coastal areas. The purpose of this study was to analyze the potential for developing adaptive fish cages farming as a form of adaptation to the impact of tidal flooding and climate change. This research was conducted in Bandengan Village, Pekalongan City from July to August 2022. The research method used was descriptive qualitative with purposive sampling and then a SWOT analysis was carried out. The results showed that the water quality parameters at the aquaculture location were still feasible and suitable for fish farming activities. Then, for harvest productivity indicators, it was still quite appropriate and profitable for this operational business cycle. Furthermore, from the analysis of internal business factors identification, 6 elements of strength and 4 elements of weakness affected the operation of fish farming. Meanwhile, from the identification of external business factors, there were 5 elements of opportunity and 2 elements of threats that could affect the operational aquaculture cycle. From the results of SWOT matrix analysis, by comparing the elements of business opportunities, weaknesses, strengths, and threats, a comparison point was obtained between 2.04 and 1.38, or it was in first quadrant in SWOT matrix, meaning good strength to be developed further. In conclusion, fish farming activities with the concept of adaptive cages were very feasible and profitable to be developed in coastal areas that are vulnerable to tidal flooding and climate change effects.Key words: Coastal, Climate change, Development, Fish aquaculture, SWOT